Developing a mechanistic translational PK/PD model for a trifunctional NK cell engager to predict the first‐in‐human dose for acute myeloid leukemia - Siak‐Leng Choi; Delphine Valente; Angela Virone‐Oddos; Christine Mauriac (Wiley, 2024)
Abstract Natural killer cell engagers (NKCEs), a treatment that stimulates innate immunity, have lately gained attention owing to their favorable safety profile, and their efficacy. Natural killer (NK) cell activation is driven by immune synapse formation between drugs, NK cells, and tumor cells. However, no clear translational modeling approach has been reported for first‐in‐human (FIH) dose estimation of humanized NKCEs. We developed the first translational mechanistic synapse‐driven pharmacokinetic/pharmacodynamic (PK/PD) model for a trifunctional NKp46/CD16a‐CD123 (CD123‐NKCE) by integrating (i) in vitro target cell cytotoxicity in MOLM‐13 tumor cell lines at varying effector‐to‐tumor cell ratios and incubation intervals; (ii) nonhuman primate PK and profiles of CD123+ cells and NKP46+ NK cells; and (iii) healthy human or patients with acute myeloid leukemia system‐specific parameters. To depict direct tumor cell killing by the innate immunity, no transit compartment was included in PK/PD model structures. Model predictions suggested an intrapatient dose escalation of 10/30/100 μg/kg twice weekly to be selected as the starting dose in the FIH trial. However, sensitivity analyses revealed that CD123+ cell growth rate constant and maximal tumor killing rate constant were the key uncertainties to the recommended active dose. This novel translational model structure can be used as the basis to predict clinical PK/PD data for CD123‐NKCE, and the translational strategy may serve as a foundation for future advancements of NKCEs.